ANALISA ERGONOMI PADA TUNGKU MASAK GULA MERAH MASYARAKAT CILONGOK KABUPATEN BANYUMAS - Ngadiman ngadiman; Siti Harwanti; Nur Ulfah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Employment in the informal sector has a major role in the developing countries including Indonesia. One group of informal workers in Banyumas is a community producer of palm sugar or brown sugar in Cilongok. In the process of making brown sugar, the furnace is one of the main facilities. Based on field observations used furnace is still a simple form and have not considered the aspect of ergonomics. The purpose of this research is to redesign the furnace to cook brown sugar-anthropometry ergonomics approach. Research using observational approaches. Anthropometric data obtained by direct measurement, while the interviews conducted to determine musculoskeletal complaints with a structured questionnaire from the Nordic Body Map. The results showed that 1) all respondents (100%) felt pains in the lower back and waist, 2) anthropometric measures of workers who made ​​reference to the determination of height is a measure of furnace design standing elbow height of 95.03 cm with a value of 90.97 percentil 5th cm, and 3) recommendations for an ergonomic cooking furnace size is the height of the furnace 80 cm, 60 cm diameter furnace, the fire hole diameter of 20 cm. Kata kunci : ergonomic, red sugar cookingKesmasindo. Volume 4(2) Juli 2011, hlm. 94-104